2020
DOI: 10.2147/cia.s255454
|View full text |Cite
|
Sign up to set email alerts
|

<p>Understanding Interactions Between Caregivers and Care Recipients in Person-Centered Dementia Care: A Rapid Review</p>

Abstract: Background Good interactions are essential in caring for people with dementia. There is a lack of knowledge about interaction approaches used by caregivers in person-centered dementia care. This study aimed to understand interactions in person-centered dementia care. Methods A search for relevant publications was undertaken in 2020 on two electronic databases, MEDLINE with full text and CINAHL Plus with full text. This was supplemented by manual searching of the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Rapid reviews are considered an emerging approach in health technology assessment to support informed decision‐making in a timely manner (Khangura et al, 2014). This methodology utilizes processes similar to a systematic literature review but limits its scope and various aspects of synthesis (Wu et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Rapid reviews are considered an emerging approach in health technology assessment to support informed decision‐making in a timely manner (Khangura et al, 2014). This methodology utilizes processes similar to a systematic literature review but limits its scope and various aspects of synthesis (Wu et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also drawn similar conclusion. For example, Chenoweth and Wu et al [38,39] also found that collaboration between departments and team members were favorable for fostering a positive environment for meaningfulness interactions between caregivers and older people. A Lack of trusting relationships and time constraints are barriers for successfully implementing PCC in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1980’s, Kitwood (1988 , 1993) pioneered a seminal paradigm shift to create a more ethnocentric approach to dementia research and person-centered care (PCC) within this particular patient population ( Wu et al, 2020 ). In contrast to the pervasive misconception in which this population suffers an inexorable loss of self ( Halewood, 2016 ), this approach reframes the individual with dementia “as a person in the fullest possible sense: he or she is still an agent, one who can make things happen in the world, a sentient, relational and historical being” ( Kitwood, 1993 , p. 541).…”
Section: Caregiversmentioning
confidence: 99%
“…Specific training programs utilizing Kitwood’s framework of person-centered dementia care have been expounded upon by numerous researchers in attempts to implement the principles critical for success into practice. A recent review article evaluated several of the components of these models, [e.g., Brooker (2003) VIPS model; Edvardsson et al (2008) six components PCC; Love and Pinkowitz (2013) four component model; and the relationship-centered care models by Nolan et al (2004) and Adams and Gardiner (2005) , and identified three main positive outcomes of PCC within the dyad, (1) social well-being; (2) psychological well-being; and (3) physical well-being ( Wu et al, 2020 )]. While promising, there remains a lack of research on person-centered care implementation into nursing home care ( Boersma et al, 2019 ).…”
Section: Policymentioning
confidence: 99%